Problematika Kepastian Hukum Barang Sitaan Aset Bukan Milik Terdakwa yang Disita oleh Kejaksaan - Putu Ayu Veguita Putri Ningsih; Slamet Tri Wahyudi (Lembaga Yasin AlSys, 2026)
Indonesia, as a constitutional rule-of-law state, upholds the principles of legal certainty and legality, including in criminal law enforcement to eradicate corruption. However, the recovery of state financial losses through asset seizure mechanisms often raises juridical polemics, particularly when coercive measures are taken against property that has not been proven to be directly related to a criminal offense or belongs to a third party acting in good faith. This study aimed to analyze the harmonization of regulations on the seizure and return of state assets in corruption cases and to assess the role of pretrial proceedings as an instrument of judicial control over seizure actions. This study used a normative juridical legal method with statutory and conceptual approaches through an examination of normative synchronization in Law No. 31/1999, Law No. 8/2010, Law No. 1/2023, and Law No. 20/2025. The results showed that although recent regulations, such as Law No. 20/2025 and Attorney General Regulation No. 7/2020, grant broad authority to prosecutors to conduct seizures from the early investigation stage in order to prevent asset dissipation, there remain legal gaps that may potentially violate the lawful property rights of suspects if asset identification and verification are not carried out transparently and accountably. Therefore, optimizing the pretrial institution is crucial for examining the validity and relevance of seized goods, so that the recovery of state finances remains within the corridor of fair legal certainty and does not turn into an arbitrary act of economic oppression by the state.